The case for conducting first-in-human (phase 0 and phase 1) clinical trials in low and middle income countries - Kapiriri Lydia; Lavery James V; Singer Peter A; Mshinda Hassan; Babiuk Lorne; Daar Abdallah S (BMC, 2011)
Abstract Background Despite the increase in the number of clinical trials in low and middle income countries (LMICs), there has been little serious discussion of whether First in Human (FIH; phase 0 and phase 1) clinical trials should be conducted in LMICs, and if so, under what conditions. Based on our own experience, studies and consultations, this paper aims to stimulate debate on our contention that for products meant primarily for conditions most prevalent in LMICs, FIH trials should preferably be done first in those countries. Discussion There are scientific and pragmatic arguments that support conducting FIH trials in LMIC. Furthermore, the changing product-development and regulatory landscape, and the likelihood of secondary benefits such as capacity building for innovation and for research ethics support our argument. These arguments take into account the critical importance of protecting human subjects of research while developing capacity to undertake FIH trials. Summary While FIH trials have historically not been conducted in LMICs, the situation in some of these countries has changed. Hence, we have argued that FIH should be conducted in LMICs for products meant primarily for conditions that are most prevalent in those contexts; provided the necessary protections for human subjects are sufficient.